2020
DOI: 10.1016/j.numecd.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Self-management education may improve blood pressure in people with type 2 diabetes. A randomized controlled clinical trial

Abstract: Background and aims: Diabetes is a suitable model to evaluate intervention programmes aimed at chronic diseases, because of its well-defined and measurable process and outcome indicators. In this study, we aimed at investigating the effects of group based selfmanagement education on clinical and psychological variables in type 2 diabetes. Methods and results: Four-year randomized controlled clinical trial (ISRCTN14558376) comparing Group Care and traditional one-to-one care. Clinical and psychological variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…However, we also feel a large responsibility to fight therapeutic inertia given the evidence for severeand even potentially life-threatening-HEs due to an avoidable high rate of LHs. We feel that a new structured education approach that is specifically designed for the elderly should be implemented on an experimental basis, possibly based on models showing effectiveness for other purposes, like the so-called ''group care'' model [28,29]. It is notable that even showing patients their lesions during US scanning procedures has proven to be quite convincing and educationally compelling per se [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, we also feel a large responsibility to fight therapeutic inertia given the evidence for severeand even potentially life-threatening-HEs due to an avoidable high rate of LHs. We feel that a new structured education approach that is specifically designed for the elderly should be implemented on an experimental basis, possibly based on models showing effectiveness for other purposes, like the so-called ''group care'' model [28,29]. It is notable that even showing patients their lesions during US scanning procedures has proven to be quite convincing and educationally compelling per se [8].…”
Section: Discussionmentioning
confidence: 99%
“…It can help patients develop skills to manage diseases more effectively and is now considered an essential part of chronic condition management (Taylor et al, 2014). A great deal of studies shows the impact of self‐management on chronic disease outcomes, including improvement of treatment adherence (Poowuttikul & Seth, 2020), symptom control (Trento et al, 2020), quality of life (Lenferink et al, 2017), and healthy behaviour factors (Dye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hildrum et al found that patients with anxiety and depression had higher diastolic blood pressure at 11-year follow-up in these populations, but presented lower diastolic blood pressure at 22-year follow-up, which may be related to antidepressants ( 50 ). Trento found that self-management education improved blood pressure in patients with type 2 diabetes ( 51 ). These factors are also present in patients with depression.…”
Section: Discussionmentioning
confidence: 99%